AKTIVITAS ANTIBAKTERI FRAKSI-FRAKSI EKSTRAK SIRIH HIJAU (Piper betle Linn) TERHADAP PATOGEN PANGAN [Antibacterial Activity of Fractionated Green Sirih (Piper betle Linn) Extract Against Food Pathogenic Bacteria] - . Suliantari; Betty S. L. Jenie; Maggy T. Suhartono (Jurnal Teknologi dan Industri Pangan, 2012)
Fractionation of green sirih (Piper betle Linn) extract by chromatography colom using the mixture of several solvents i.e. chloroform, ethanol and acetic acid (4:1:1) resulted in 17 fractions. All fractions showed antibacterial activities but only 2 fractions (fraction 3 and fraction 4) showed the highest inhibition towards the six tested bacteria Escherichia coli, Salmonella Typhimurium, Pseudomonas aeruginosa, Staphylococcus aureus, Bacillus cereus and Listeria monocytogenes. Among the tested bacteria, all fractions of green sirih extracts showed the most effective inhibition against, Salmonella Typhimurium with inhibition zone diameters ranging from 10 mm to 26 mm. Identification using GC-MS found that fraction 3 and fraction 4 contained chavicol; dodecanoic acid, myristic, palmitic and oleic acid.